The objectivity of lifeworld and everyday experiences of people with mental disorders - Mesquita Soares de Araujo, Bruno (Sociologias Plurais, 2024)
This article aims to adapt Alfred Schütz's sociological approach to understanding the everyday experiences of people with mental disorders. According to Schütz, common sense encompasses objective knowledge that organizes societal experiences in everyday life. When this objective knowledge is disrupted, the everyday lives of those affected can be significantly impacted. Due to these impacts, efforts in mental health care should focus on understanding the dilemmas faced by its users in their daily routine and incorporating their everyday needs into healthcare practices. In order to highlight these issues, this paper is divided into four parts. The first section introduces phenomenology and its relevance in understanding Schütz's social theory and everyday life experiences. The subsequent section explores Schütz's inquiry into the objectivity of the lifeworld in everyday experiences. The third section delves into the significance and challenges faced by individuals with mental disorders in their daily lives. The final section introduces the concept of insanity policy, highlighting potential avenues for health professionals and policymakers to integrate the everyday experiences of people with mental disorders into mental healthcare. Special attention is given to differentiating between care in everyday life and the everyday life of care.